2016
DOI: 10.1007/s10278-016-9911-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists’ Variation of Time to Read Across Different Procedure Types

Abstract: The workload of US radiologists has increased over the past two decades as measured through total annual relative value units (RVUs). This increase in RVUs generated suggests that radiologists' productivity has increased. However, true productivity (output unit per input unit; RVU per time) is at large unknown since actual time required to interpret and report a case is rarely recorded. In this study, we analyzed how the time to read a case varies between radiologists over a set of different procedure types by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Similarly, to other recently published surveys, the present study demonstrated an annual increase of 3.9% in the number of radiology reports and imaging examinations during the evaluation period in 2018 compared to 2017 (Table 1 ) [ 3 , 12 , 13 ]. Interestingly, there was an increase from 37,247 to 38,754 reports but a decrease in reports with a second signature from 16,632 to 15,967 reports (Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, to other recently published surveys, the present study demonstrated an annual increase of 3.9% in the number of radiology reports and imaging examinations during the evaluation period in 2018 compared to 2017 (Table 1 ) [ 3 , 12 , 13 ]. Interestingly, there was an increase from 37,247 to 38,754 reports but a decrease in reports with a second signature from 16,632 to 15,967 reports (Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…In the United States, a recent paper by Forsberg, Rospiko and Sunshine directly measured radiologist reporting time for a range of studies reported in 2015 within a system of several linked hospitals. The focus of the paper was radiologist reading time variability.…”
Section: Discussionmentioning
confidence: 99%
“…At treatment hospitals, radiologists need to carefully compare opacities on CT scans across time to alert cases suspected of deterioration. 19 Time pressure, heavy workload, and a shortage of experienced radiologists resulted in challenges for imaging-based management of COVID-19.…”
Section: Introductionmentioning
confidence: 99%